How to facilitate the implementation of 3D models in China by applying good in vitro method practice for regulatory use - Liu, Yanfeng; Cai, Zhenzi; Li, Nan; Alépée, Nathalie (Frontiers in Toxicology, 2023)
OECD Guidance Documents No. 34 and No. 286 on Good In Vitro Method Practices (GIVIMP) for the development and implementation of in vitro methods for regulatory use in human safety assessment have been endorsed. Considering that China is accelerating the development of alternative approaches in both research and acceptance, application of these principles is therefore primordial for the implementation and acceptance of in vitro alternatives methods in China. To promote the replacement of animal testing for regulatory use, L’Oréal initiated the EpiSkin™ skin irritation test (SIT) implementation program in China. More than 50 external scientists participated, and the method has been established in 34 organizations including authority, industry and testing service laboratories. Taking two collaborations with Guangdong CDC and Shanghai SGS for in vitro SIT as examples, we demonstrated a method implementation process in good alignment with OECD principles. The current study illustrated the practical way in which both OECD guidances can assist in the transfer and establishment of in vitro approaches, and further promoted the future scientific recognition and acceptance of new alternative methodologies OECD accepted testing methods in China.